DESIGNING THE FISWR LEARNING MODEL: EMPOWERING ENGLISH LEARNERS THROUGH VOCABULARY MASTERY AND PEER COLLABORATION - Naibaho, Lamhot; Tehupoeiory, Aarce; Tambunsaribu, Gunawan; Siregar, Geby Arny (English Review: Journal of English Education, 2025)
The recent Covid-19 pandemic has forced universities to quickly adapt to conditions requiring the modernization of their learning systems through technology. Alongside these demands, universities must also maintain or enhance students' academic achievements. This presents significant challenges due to various internal and external problems faced by institutions. However, universities have taken numerous steps to maximize their potential and improve academic outcomes. To address these challenges effectively, universities must implement immediate solutions. A key approach is the development of adaptable learning models that can be applied both online and offline. This research focuses on developing an English language learning model. The study employs a Research and Development (RnD) design and will be conducted at the Indonesian Christian University. The objectives of this research are: a) to empirically identify the learning models students need; b) to empirically assess the feasibility of these models from the perspective of relevant experts; c) to empirically evaluate the effectiveness of the developed models; and d) to empirically analyze students' perceptions of the developed models. The expected outcome of this research is the production of fully developed learning models that are ready for implementation in universities.